Manfaat Ekstrak Buah Adas (Foeniculum vulgare) Terhadap Bakteri Cutibacterium acnes - Amourisva, Azqiya Putri; Carolia, Novita (CV. Jasa Sukses Abadi, 2024)
Fennel fruit (Foeniculum vulgare) is known for its antibacterial properties, making it a promising natural remedy for acne treatment, particularly against Cutibacterium acnes, the primary acne-causing bacterium. The increasing issue of antibiotic resistance highlights the need for safer and more effective natural alternatives. The essential oil of fennel contains major compounds such as anethole (83.64%), fenchone (3.58%), and l-limonene (3.75%), which have been shown to exhibit significant antibacterial activity. Research indicates that a 2% fennel oil concentration produces an inhibition zone of 7.5 mm, while an 8% concentration increases this to 19 mm, demonstrating its effectiveness in inhibiting bacterial growth. In addition to its antibacterial activity, fennel extract also possesses anti-inflammatory properties, which help reduce inflammation and redness caused by acne. Fennel oil-based cream formulations have also been developed, showing good physical stability and strong antibacterial effects against C. acnes. One key advantage of fennel extract is its natural composition, making it safer compared to synthetic antibiotics, which may cause side effects and bacterial resistance. Therefore, fennel extract holds great potential as an active ingredient in anti-acne skincare formulations. However, further research is necessary to confirm its long-term efficacy and applications in cosmetic and pharmaceutical formulations to ensure its safety and benefits for long-term use.